Impact of malocclusion on the quality of life of children aged 8 to 10 years - Sônia Rodrigues Dutra; Henrique Pretti; Milene Torres Martins; Cristiane Baccin Bendo; Miriam Pimenta Vale
ABSTRACT Objective: The aim of the present cross-sectional study was to assess the impact of malocclusion on the quality of life of children aged 8 to 10 years attending public elementary schools in Belo Horizonte, State of Minas Gerais, Brazil. Methods: The Brazilian version of the Child Perceptions Questionnaire 8-10 (CPQ8-10) was used to evaluate oral health-related quality of life. The children were examined for the diagnosis of malocclusion using the Dental Aesthetic Index (DAI). The data were analyzed by bivariate and multivariate descriptive statistics using Poisson regression at a 5% significance level. A total of 270 children participated in the study. Results: Children with normal occlusion or mild malocclusion (DAI ≤ 25) were 56% less likely (95%CI: 0.258-0.758; p= 0.003) to have their quality of life affected compared with children diagnosed with extremely severe malocclusion (DAI ≥ 36). Children with a maxillary anterior overjet ≥ 3 mm had higher CPQ8-10 mean scores (19.4; SD = 17.1) than those with an overjet < 3 mm (13.6; SD = 11.7; p= 0.038). Conclusions: Extremely severe malocclusion and pronounced maxillary anterior overjet were associated with a negative impact on quality of life.